The benefit of using the comparative method in studying public adminitration - Korczak, Jerzy (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The article focuses on the origins and history of comparatist studies, the objectives of this research method, especially as regards administrative law, as well as possible results of its use, which can be used in legislation, practice administrative, case-law, and finally in the study of administrative phenomena. A separate thread of the article is the presentation of the achievements of Wroclaw school of administration, whose particular feature is the use of administrative comparatist.
Keywords: public administration; Wrocław school od administration; comparative method